(3GdeSGdc aj TQM ehWC eGdcs - (3eMeO Hf YHO Gddg Hf eMeO GdeYGaQj GdETHjdj GdeGdcj, GdbGVj CHh HcQ GHf GdYQHqj , J (B543 (3g` s ((3YeQ Hf jhSa GdafGfi s)
(3ChdgG (B:s
(3jHOC HcJGH GdLgGO hCMcGeI hajg KdGK eSGFd (B: (3GdChdi ai GSJbGbI dZI s
(3BNQgG (B:s
(3GdcdGe Ydi CSeGA GdfHi Udi Gddg Ydjg hSde hCfG CYJPQ Edi cd ef fXQ ajg hJUaMI s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B230s
Keywords: (3eJaQbGJs